2017
DOI: 10.1002/btpr.2463
|View full text |Cite
|
Sign up to set email alerts
|

Epitopes rationally selected through computational analyses induce T‐cell proliferation in mice and are recognized by serum from individuals infected with Schistosoma mansoni

Abstract: Schistosomiasis is the second leading cause of death due to parasitic diseases in the world. Seeking an alternative for the control of disease, the World Health Organization funded the genome sequencing of the major species related to schistosomiasis to identify potential vaccines and therapeutic targets. Therefore, the aim of this work was to select T and B-cell epitopes from Schistosoma mansoni through computational analyses and evaluate the immunological potential of epitopes in vitro. Extracellular regions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 70 publications
(150 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, in silico discovery of immunoreactive B cell epitopes may allow the design of species-specific epitopes for serological diagnosis. Moreover, the possibility of construction of multi-epitopic chimeric proteins could improve the diagnostic accuracy of synthetic peptides [ 37 , 70 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in silico discovery of immunoreactive B cell epitopes may allow the design of species-specific epitopes for serological diagnosis. Moreover, the possibility of construction of multi-epitopic chimeric proteins could improve the diagnostic accuracy of synthetic peptides [ 37 , 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the present review, we identified two studies [ 16 , 37 ] that investigated peptide based serum IgG ELISA and one study [ 36 ] that utilized a multi-peptide chimeric protein. Except for Smp_167240 (213–228), Smp_141860 (1694–1709), Smp_141860 (1694–1706) and Sm 156860 which had poor diagnostic performances most peptides identified in this review had good diagnostic performances with sensitivities ranging from 67.71% to 96.15%, specificities ranging from 69.23% to 100% and AUC ranging from 0.76 (95% CI 0.6024–0.9213) to 0.99 (95% CI 0.987–100) ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Carvalho and colleagues, 2022 and Lopes and colleagues, 2017 had previously used immunoinformatic approaches and immune-assay validation to identify S. haematobium and S. mansoni peptides with diagnostic potential (18,19). This study identified one peptide (AA81008-19-30) that had an excellent diagnostic performance for discriminating S. mansoni positives from healthy controls for IgG.…”
Section: Discussionmentioning
confidence: 99%
“…Eighteen previously published peptides were included on the peptide microarray, 10 from our previous study Vengesai and colleagues, 2022 (26) and 8 peptides from two studies by Carvalho and Colleagues, 2022 and Lopes and Colleagues, 2017 (18,19). Despite Carvalho and Colleagues, 2022 and Lopes and Colleagues, 2017 showing that peptides Sm168240, Smp_136560 (1564–1578), Smp_126160(438–452), Sm140560, Sm041370, Smp_180240(339–353), Smp_150390.1(216–230), Smp_093840(219–233) had AUC values ranging from 0.76 (95 % CI 0.6024-0.9213) to 0.99 (95 % CI 0.987-100) results from this current study show that only one published peptide Smp 126160-438-452 had an acceptable diagnostic performance with an AUC value of 0.7115 (95% CI 0.605-0.82218).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation